Management of complications in common hand and wrist procedures FESSH instructional course book 2021 - Heijden, Brigitte van der, 1967-; Haugstvedt, Jan-Ragnar, 1954-; Coert, Henk, 1967- (Thieme, 2022)
"Operative complications can have a major impact on patients and surgeons. While most textbooks list them, few provide in-depth discussion on prevention, repercussions, and methods to resolve them. Management of Complications in Common Hand and Wrist Procedures: FESSH Instructional Course Book 2021, edited by renowned hand surgeons Brigitte van der Heijden, Jan-Ragnar Haugstvedt, and Henk Coert, features contributions from an impressive group of international hand surgery experts. This book provides in-depth, illustrated coverage on the prevention and management of complications that can occur during common hand and wrist approaches. It also provides insights on how meticulously performed hand therapy can help alleviate postsurgical problems, on the complex regional pain syndrome (CRPS), and on critical social issues"--